Sistem Pencatatan Keuangan Berbasis Website Menggunakan Metode RAD Pada PT. Buditani Kembangjaya - ,; , (Jurnal Mahasiswa Aplikasi Teknologi Komputer dan Informasi (JMApTeKsi), 2025)
PT. Buditani Kembangjaya is a company engaged in palm oil sales. Currently, the company's financial recording is still done manually using spreadsheets and notebooks, leading to various challenges such as inefficiency, risk of recording errors, and difficulties in preparing financial reports. Therefore, a web-based financial recording system is needed to improve efficiency, accuracy, and transparency in financial data management. This study aims to design and develop a web-based financial recording system using the Rapid Application Development (RAD) method. The RAD method was chosen because it allows for faster and more flexible system development through iterative cycles, ensuring that the system can be optimally adapted to the company's needs. The developed system includes features for recording financial transactions, managing financial reports, and presenting real-time data to support more precise business decision-making. The results of this study indicate that the web-based financial recording system can help PT. Buditani Kembangjaya manage financial transactions more efficiently and accurately. The implementation of this system minimizes recording errors, speeds up the preparation of financial reports, and provides well-structured and easily accessible financial information. Thus, this system can be an effective solution for improving the company's financial management .